Pengembangan Kompetensi PTK Guru PAI SMP/ MTs di Kabupaten Sleman - Siti Aminah (Academy of Education Journal, 2026)
This study aims to analyze the development of Classroom Action Research (CAR) competence among Islamic Religious Education teachers at junior secondary schools and Islamic junior secondary schools in Sleman Regency, identify the determinants of training success, and formulate strategies for strengthening product based CAR training. The study was motivated by the suboptimal training outputs, including CAR proposals categorized as good that reached only 33% and career impact that appeared in only 7.5% of alumni. The study employed a sequential explanatory mixed methods design. Quantitative data were collected from 35 Islamic Religious Education teachers who had participated in CAR training, while qualitative data were obtained through open interviews, document review, and explanatory follow up of the quantitative findings. The findings show that teachers mastery of CAR competence falls into the categories of mastered and sufficiently mastered, but has not reached an optimal level, particularly in developing instruments, reviewing theories, analyzing previous studies, determining classroom actions, and managing references. The study also identified the need to integrate 15 new competencies, especially digital technology, higher order thinking skills, innovative learning models, twenty first century skills, learning assessment, and noble character values. Training success was found to be systemic, involving committee readiness, curriculum relevance, technological facilities, trainer competence, participant engagement, and evaluation of action plan implementation. The article recommends product based CAR training supported by clinical mentoring, academic review, and sustainable post training monitoring.